Jakartans' Perceptions of Health Care Services - Sokang, Yasinta Astin; Westmaas, Alvin Henry; Kok, Gerjo (Frontiers in Public Health, 2019)
Health Care Services (HCSs) should implement ongoing innovation and continuously improve their quality. However, in evaluating the quality of HCSs, too little attention has been given to the experience of the users concerning the acquired services. This study focused on how the community values the current services in order to improve HCSs in Indonesia, especially in Jakarta. Four focus group discussions were conducted among 45 community members in the Grogol Petamburan sub-district, in Jakarta. Participants were recruited using a convenience sampling and the data were analyzed using a combination of human coding and NVivo-12. Overall, we found that participants had a negative view on the government-mandated Community Health Centers (CHCs) and they preferred to visit private clinics and hospitals over the CHCs. Participants associated CHCs with unfriendly staffs, longer waiting time, shorter opening hours, and crowded visitors. At the same time, participants had a positive view on the affordability of the CHCs. Additionally, we found the reasoning of Jakartans’ (i.e., the citizens of Jakarta city) on using self- and traditional treatments before visiting HCSs and they also expressed the need for psychological services at CHCs. The discussion focuses on the results as feedback on how the government and health care providers may facilitate the community’s needs in providing HCSs in Indonesia, especially Jakarta. In brief, we recommend the policy-makers to improve the hospitality of the staff members and the quality of the medical equipment; also, to provide psychological services at CHCs. These efforts need to be done while paying more attention to the cultural aspects of medicinal uses.